Asia changing the world (Verl. Bertelsmann Stiftung, 2007)
Preface / Liz Mohn, Wolfgang Schüssel -- Introduction / Malte C. Boecker -- I. Asia's potential as a world power. Demographic dynamics of Asia / Carl Haub -- Asia's economic and technological outlook / Horst Siebert -- Asia, Europe and the global power balance / Paul Kennedy -- II. Asia's challenges. Inner-Asian fragilities / Aurel Croissant -- Asian mobility and Europe : managing and benefiting from a near inevitability / Demetrios Papademetriou -- Is it possible to sustain Asia? / John Elkington, Jodie Thorpe -- III. Asia's soft power. Perspectives on the economic and human development of India and China / Amartya Sen -- Asia civilization and culture in a globalized world / Karan Singh -- The cultural diplomacy of East Asian nations / Kazuo Ogoura -- Where is Chinatown? / Eduard Kögel -- The future of classical music depends on Asia / Delfín Colomé -- Asia and Europe : competition or spiritual synthesis? / Michael von Brück -- IV. Answers to Asia. Cultural foreign policy : opportunity for Asia and Europe / Hans-Georg Knopp -- An open, innovative Europe for a global world / José Manuel Barroso -- An equal partnership in the 21st century : Europe's answer to Asia's challenges / Pascal Lamy -- Requirements for a European Asian strategy / Werner Weidenfeld